2017
DOI: 10.1177/0267658317694221
|View full text |Cite
|
Sign up to set email alerts
|

The phraseological dimension in interlanguage complexity research

Abstract: This article reports on the first results of a large-scale research programme that aims to define and circumscribe the construct of phraseological complexity and to theoretically and empirically demonstrate its relevance for second language theory. Within this broad agenda, the study has two main objectives. First, it investigates to what extent measures of phraseological complexity can be used to describe second language (L2) performance at different proficiency levels. Second, it compares measures of phraseo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 51 publications
8
93
2
4
Order By: Relevance
“…Avenues which immediately suggest themselves for further exploration include integrating syntactic variables beyond simple part of speech analysis, and integrating phraseological analysis. Research in second language writing has shown categories such as collocation to be important aspects of development and to provide novel perspectives on learner language (e.g., Biber & Gray, 2013;Chen & Baker, 2016;Paquot, 2017). However, this work has been almost entirely ignored in studies of first language writing development.…”
Section: Discussionmentioning
confidence: 99%
“…Avenues which immediately suggest themselves for further exploration include integrating syntactic variables beyond simple part of speech analysis, and integrating phraseological analysis. Research in second language writing has shown categories such as collocation to be important aspects of development and to provide novel perspectives on learner language (e.g., Biber & Gray, 2013;Chen & Baker, 2016;Paquot, 2017). However, this work has been almost entirely ignored in studies of first language writing development.…”
Section: Discussionmentioning
confidence: 99%
“…This measure calculates an association score for the relationship between the first two words and the third word in a trigram. Although findings from cross‐sectional research have indicated that MI score tends to increase and that t‐score tends to decrease with increasing language proficiency (Bestgen & Granger, ; Granger & Bestgen, ; O'Donnell, Römer, & Ellis, ; Paquot, ), longitudinal research has found very little development in bigram association scores even after extended periods of study (Bestgen & Granger, ; Li & Schmitt, ). In both Bestgen & Granger () and Li & Schmitt (), only t‐score showed change over time, and the effect was small in both studies.…”
Section: Methodsmentioning
confidence: 99%
“…Studies that calculate MWS association strength scores using L1 reference corpus frequency data have also demonstrated that more proficient L2 writers produce more target‐like bigrams and collocations. Specifically, research reports that more proficient L2 writers produce more bigrams and collocations with high MI scores (Bestgen & Granger, ; Granger & Bestgen, ; Paquot, ). Less proficient learners, on the other hand, have been shown to rely more on high t‐score bigrams, non‐collocation bigrams, and bigrams that occur too infrequently in reference corpora for association strength calculation (<5 occurrences) (Granger & Bestgen, ).…”
Section: L2 Phraseology In Learner Corporamentioning
confidence: 99%
“…In the field of SLA research, there is a growing interest in investigating the relationship between the use of MWSs and L2 proficiency (Boers & Webb, ), which has been motivated by the strong theoretical and empirical psycholinguistic evidence discussed above. However, the majority of studies in this area have focused on written production using an essay‐writing task (e.g., Bestgen & Granger, ; Durrant & Schmitt, ; Granger & Bestgen, ; Kim, Crossley, & Kyle, ; Kyle & Crossley, ; Kyle, Crossley, & Berger, ; Laufer & Waldman, ; Paquot, ; Siyanova‐Chanturia & Spina, ). The findings of these studies suggest that L2 writers of higher proficiency, compared to those of lower proficiency, tend to have richer phraseological knowledge as well as better control of MWSs in communication.…”
Section: Background Literaturementioning
confidence: 99%
“…One line of research in this area has focused on the use of multiword sequences (MWSs)—combinations of words that appear together highly frequently in a target language (Garner & Crossley, )—and on its relationship with proficiency (e.g., Nattinger & DeCarrico, ; Pawley & Syder, ; Wood, ; Wray, ; see Granger, , for a review). Findings suggest that more proficient L2 users have a better command of MWSs in terms of range, frequency, and sophistication (e.g., Durrant & Schmitt, ; Garner & Crossley, ; Kyle & Crossley, ; Paquot, ). The findings also indicate that use of MWSs is related to oral fluency (Boers, Eyckmans, Kappel, Stengers, & Demecheleer, ; Stengers, Boers, Housen, & Eyckmans, ; Tavakoli, ; Wood, , ).…”
Section: Introductionmentioning
confidence: 99%